The Implementation Of Visual Media In The Form Of Images In Indonesian Language Learning For Elementary Schools - Majdi, Muhammad; Hartati, Leni; Nahda, Maisah (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
Visual media, such as images, plays a crucial role in Indonesian language learning at the early stages (Grades 1 and 2), particularly in the topic of